2019
DOI: 10.1080/13504509.2019.1655111
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in manufacturing processes: practices performed in metal forming, casting, heat treatment, welding and electrostatic painting

Abstract: This article aims to list the main sustainable practices developed in the processes of metal forming, casting, heat treatment, welding and electrostatic painting. When analysed the literature about sustainable manufacturing, a predominance of studies about machining is observed and the processes mentioned are few explored in academic studies. The research strategy used to reach the objective was systematic literature review, conducted for each process cited. Many sustainable practices were identified with prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…The conservation of resources and energy are the key enablers of sustainable development, and the design of lightweight structures and manufacturing are directed to fulfill this aim [1,2]. High-quality and high-strength aluminum alloys are the materials of choice in developing lightweight structures.…”
Section: Introductionmentioning
confidence: 99%
“…The conservation of resources and energy are the key enablers of sustainable development, and the design of lightweight structures and manufacturing are directed to fulfill this aim [1,2]. High-quality and high-strength aluminum alloys are the materials of choice in developing lightweight structures.…”
Section: Introductionmentioning
confidence: 99%
“…Qorri et al [38] indicated that social sustainability-related initiatives are difficult to evaluate; however, researchers are taking the lead to develop meaningful measures as a way to begin benchmarking performance. Social sustainability might be achieved when firms adopt measurable SSCM related initiatives in hopes of contributing to social performance [39]. Since companies should function more responsibly and look after worker health, safety, and work conditions, it emphasizes on the point that social sustainability should be treated as an important topic in SCM [40].…”
Section: Sustainable Supply Chain Managementmentioning
confidence: 99%
“…Cleaner Production (CP) is the application of a technical, economic and environmental strategy integrated to processes and products in order to increase the efficiency in the use of raw materials, water and energy by preventing, minimizing or recycling waste and emissions, with environmental, economic and occupational health benefits (UNEP, 2006;Nobrega et al, 2019).…”
Section: Cleaner Production (Cp)mentioning
confidence: 99%
“…According to De Oliveira (2013), the integration of Quality System, Environmental Management and Occupational Safety and Health is important in the context of Cleaner Production. Many economic and environmental advantages resulting from CP can be cited (Nobrega et al, 2019):…”
Section: Cleaner Production (Cp)mentioning
confidence: 99%
See 1 more Smart Citation